2016
DOI: 10.2217/nnm-2016-0173
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and Protein Corona Formation on Gold Nanoparticles Affect Viability and Liver Functions of Primary Rat Hepatocytes

Abstract: The AuNP-Cor showed higher cell uptake and reduced cell viability compared with aggregated AuNP-Cit. Urea and albumin secretions showed AuNP dose dependency. Both AuNP-Cit and AuNP-Cor exerted only an acute effect on the albumin synthesis of hepatocytes with no chronic impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…All GO samples showed hydrodynamic diameter sizes of 320–460 nm in RPMI 1640 medium compared to a size range of 550–600 nm in BEGM medium; the reduced size in the former medium is due to the presence of a high concentration of serum albumin, which leads to the formation of a protein corona. 19, 20…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All GO samples showed hydrodynamic diameter sizes of 320–460 nm in RPMI 1640 medium compared to a size range of 550–600 nm in BEGM medium; the reduced size in the former medium is due to the presence of a high concentration of serum albumin, which leads to the formation of a protein corona. 19, 20…”
Section: Resultsmentioning
confidence: 99%
“…Most GO samples showed agglomeration in DI H 2 O, resulting in hydrodynamic diameters of 330–440 nm, except for rGO-2 that showed larger (550 nm) agglomerates as a result of reduced hydrophilicity. All GO samples showed hydrodynamic diameter sizes of 320–460 nm in RPMI 1640 medium compared to a size range of 550–600 nm in BEGM medium; the reduced size in the former medium is due to the presence of a high concentration of serum albumin, which leads to the formation of a protein corona. , …”
Section: Resultsmentioning
confidence: 99%
“…Thus, an acute burst of exposure to GNPs is more harmful to cells, and cells can adapt to protect themselves against long-term nanoparticle exposure. Another in-vitro study on primary rat hepatocytes showed that both citrate and protein corona coated GNPs exerted only an acute effect on the albumin synthesis of hepatocytes, with no chronic impact [ 29 ]. Thus, the acute phase toxicity of GNPs after the first dose followed by the recovery phase, even after the subsequent exposure of GNPs, is in agreement with previous reports that have shown the absence of toxicity in animals that were treated with multiple doses of GNPs [ 16 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…PC-coated NPs strongly differ in size, surface charge and aggregation state compared to pristine NPs. 68 PC composition is affected by both NP characteristics (e.g., physicochemical properties) and environmental factors (e.g., temperature, protein source, type of disease present). The effect of NPs’ physicochemical properties on corona formation have been extensively examined and already comprehensively reviewed by us and others.…”
Section: Introductionmentioning
confidence: 99%